Godskonsepte tydens pastorale gesprekvoering - F. J. van Jaarsveld; J. Janse van Rensburg (Acta Theologica)
There are indications that people’s concepts of God are not adequately considered in existing models for pastoral counselling. These refer to differences among people’s concepts of God as result of their stages of life, personal constructs, and the restructering of inappropriate concepts of God. Research in this regard comprises an evaluation of relevant literature and an empirical investigation. In the literature study a theological anthropology is critically analised, a number of pastoral models evaluated, a theological basic theory formulated and a theory in practice compiled. Evaluation of the empirical research reveals important differences in concepts of God among three groups of individuals in different stages of the adult life cycle, as well as some influence of the individual’s personal construct system. These observations result in the postulation of a supplementary model for pastoral counselling.